If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + -8)(x + -2)(x + 9) = 0 Reorder the terms: (-8 + X)(x + -2)(x + 9) = 0 Reorder the terms: (-8 + X)(-2 + x)(x + 9) = 0 Reorder the terms: (-8 + X)(-2 + x)(9 + x) = 0 Multiply (-8 + X) * (-2 + x) (-8(-2 + x) + X(-2 + x))(9 + x) = 0 ((-2 * -8 + x * -8) + X(-2 + x))(9 + x) = 0 ((16 + -8x) + X(-2 + x))(9 + x) = 0 (16 + -8x + (-2 * X + x * X))(9 + x) = 0 (16 + -8x + (-2X + xX))(9 + x) = 0 Reorder the terms: (16 + -2X + -8x + xX)(9 + x) = 0 (16 + -2X + -8x + xX)(9 + x) = 0 Multiply (16 + -2X + -8x + xX) * (9 + x) (16(9 + x) + -2X * (9 + x) + -8x * (9 + x) + xX(9 + x)) = 0 ((9 * 16 + x * 16) + -2X * (9 + x) + -8x * (9 + x) + xX(9 + x)) = 0 ((144 + 16x) + -2X * (9 + x) + -8x * (9 + x) + xX(9 + x)) = 0 (144 + 16x + (9 * -2X + x * -2X) + -8x * (9 + x) + xX(9 + x)) = 0 (144 + 16x + (-18X + -2xX) + -8x * (9 + x) + xX(9 + x)) = 0 (144 + 16x + -18X + -2xX + (9 * -8x + x * -8x) + xX(9 + x)) = 0 (144 + 16x + -18X + -2xX + (-72x + -8x2) + xX(9 + x)) = 0 (144 + 16x + -18X + -2xX + -72x + -8x2 + (9 * xX + x * xX)) = 0 (144 + 16x + -18X + -2xX + -72x + -8x2 + (9xX + x2X)) = 0 Reorder the terms: (144 + -18X + 16x + -72x + -2xX + 9xX + -8x2 + x2X) = 0 Combine like terms: 16x + -72x = -56x (144 + -18X + -56x + -2xX + 9xX + -8x2 + x2X) = 0 Combine like terms: -2xX + 9xX = 7xX (144 + -18X + -56x + 7xX + -8x2 + x2X) = 0 Solving 144 + -18X + -56x + 7xX + -8x2 + x2X = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-144' to each side of the equation. 144 + -18X + -56x + 7xX + -8x2 + -144 + x2X = 0 + -144 Reorder the terms: 144 + -144 + -18X + -56x + 7xX + -8x2 + x2X = 0 + -144 Combine like terms: 144 + -144 = 0 0 + -18X + -56x + 7xX + -8x2 + x2X = 0 + -144 -18X + -56x + 7xX + -8x2 + x2X = 0 + -144 Combine like terms: 0 + -144 = -144 -18X + -56x + 7xX + -8x2 + x2X = -144 Add '56x' to each side of the equation. -18X + -56x + 7xX + -8x2 + 56x + x2X = -144 + 56x Reorder the terms: -18X + -56x + 56x + 7xX + -8x2 + x2X = -144 + 56x Combine like terms: -56x + 56x = 0 -18X + 0 + 7xX + -8x2 + x2X = -144 + 56x -18X + 7xX + -8x2 + x2X = -144 + 56x Add '8x2' to each side of the equation. -18X + 7xX + -8x2 + 8x2 + x2X = -144 + 56x + 8x2 Combine like terms: -8x2 + 8x2 = 0 -18X + 7xX + 0 + x2X = -144 + 56x + 8x2 -18X + 7xX + x2X = -144 + 56x + 8x2 Reorder the terms: 144 + -18X + -56x + 7xX + -8x2 + x2X = -144 + 56x + 8x2 + 144 + -56x + -8x2 Reorder the terms: 144 + -18X + -56x + 7xX + -8x2 + x2X = -144 + 144 + 56x + -56x + 8x2 + -8x2 Combine like terms: -144 + 144 = 0 144 + -18X + -56x + 7xX + -8x2 + x2X = 0 + 56x + -56x + 8x2 + -8x2 144 + -18X + -56x + 7xX + -8x2 + x2X = 56x + -56x + 8x2 + -8x2 Combine like terms: 56x + -56x = 0 144 + -18X + -56x + 7xX + -8x2 + x2X = 0 + 8x2 + -8x2 144 + -18X + -56x + 7xX + -8x2 + x2X = 8x2 + -8x2 Combine like terms: 8x2 + -8x2 = 0 144 + -18X + -56x + 7xX + -8x2 + x2X = 0 The solution to this equation could not be determined.
| -(3y-3)-(2y-4)=-3 | | 2b+2=2(2-r)+6 | | y^4-36y=0 | | 1+p=4 | | log(x-4)/log(3)-log(x)/log(3)=3 | | 2x^2+4x+0= | | z/10-8=10 | | U/5=95 | | x^4-2x^3-52x^2+8x+192=0 | | 2x-1=3r | | ((3a^-5b^4c^3)/(15ab^5c^-2))^3 | | 0.5(5x+9)=1.6-(x-3) | | Log(x+1)-log(x)=log(31) | | x^4-3x^3-11x^2+3x+10=0 | | 5y-1+y+37=5y+40-1y | | F(x)=x^5+2x^4+9x^3+18x^2+20x+40 | | 7x/10-1/2=x/5 | | x+6(x+4)=25 | | 16x^2-80+100=0 | | 5(y+20)=55 | | (8/4x)=21 | | -12x+18=0 | | 2x+0.6=x | | 5(x-3)/6=-2x | | 8/4x=21 | | -2x+19=0 | | F(X)=x^3+11x^2-X-11 | | 9+7lnx=65 | | 3(y+1)=36 | | 3x^2-x-784=0 | | -4(n+2)=20 | | B*13=8 |